2003
DOI: 10.1111/j.1346-8138.2003.tb00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Free Residual Chlorine in Bathing Water Reduces the Water‐Holding Capacity of the Stratum Corneum in Atopic Skin

Abstract: Some patients with atopic dermatitis (AD) develop dry skin or exacerbated cutaneous inflammations with frequent swimming in public pools or after bathing. We examined the effects of residual chlorine in bathing water on the function of the stratum corneum (SC) in patients with AD and determined the lowest chlorine concentration showing an effect. In addition, we investigated the relationship between the free residual chlorine concentration in bathing water and the water-holding capacity of the SC in patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 7 publications
1
26
0
2
Order By: Relevance
“…Eczema (or atopic dermatitis) is a chronic inflammatory skin disease characterised by the formation of specific antibodies (IgE) to environmental allergens, which frequently starts early in infancy and affects 15-30% of children in industrialised countries [25]. Although IgE blood levels were unrelated to both cumulative and acute pool exposure in two studies [26,27], a semi-experimental study suggested that dermal pool exposure may play a role in the exacerbation of atopic dermatitis [28]. Furthermore, it has been described that workers engaged in wet-works are at risk for suffering irritant dermatitis [29], which in turn may enhance the atopic dermatitis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Eczema (or atopic dermatitis) is a chronic inflammatory skin disease characterised by the formation of specific antibodies (IgE) to environmental allergens, which frequently starts early in infancy and affects 15-30% of children in industrialised countries [25]. Although IgE blood levels were unrelated to both cumulative and acute pool exposure in two studies [26,27], a semi-experimental study suggested that dermal pool exposure may play a role in the exacerbation of atopic dermatitis [28]. Furthermore, it has been described that workers engaged in wet-works are at risk for suffering irritant dermatitis [29], which in turn may enhance the atopic dermatitis [30].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Seki et al [21] conducted tests under conditions not exactly similar to pool water. Therefore, results might be different regarding pool attendance.…”
Section: Discussionmentioning
confidence: 98%
“…Seki et al [21] investigated potential effects of chlorine in bathing water on atopic and non-atopic skin In order to show this, they bathed the forearm of the participants in chlorinated water. The water-holding capacity of the stratum corneum of patients with atopic dermatitis proved to be more sensitive to free residual chlorine exposure, than that of normal control subjects.…”
Section: Chlorine and Skinmentioning
confidence: 99%
“…In einem meiner alten exzellenzbasierten Lehrbücher hatte ich noch gefunden, dass Chlorwasser bei einem recht guten Hautzustand des Neurodermitikers sogar "abhärtend" wirken könne und durchaus zu empfehlen sei. Dennoch, das freie Chlor im Schwimmbadwasser reduziert die wasserbindende Kapazität des Stratum Corneum, wie bei atopischer Haut bereits von einer japanischen Arbeitsgruppe gezeigt wurde [2].…”
unclassified